The older adults' experiences of living in the nursing home during the COVID‐19 pandemic: A qualitative study in Iran - Zahra Asgari; Azar Darvishpour (Wiley, 2023)
Abstract Aim This study aimed to describe the experiences of older adults living in a nursing home during the COVID‐19 pandemic. Design A qualitative descriptive study. Methods In present study, 20 older adults living in a nursing home in Rasht, northern Iran, participated. Purposeful sampling was applied until data saturation. The qualitative content analysis was done according to the steps proposed by Zhang and Wildemuth. Results The central theme was "Intensification of life problems in the nursing home", which emerged from the 115 primary codes, 4 main categories and 7 subcategories. The main categories included "feelings about COVID‐19," "intensification of isolation and loneliness," "imprisonment and feeling forgotten" and "difficulty in adapting". Conclusion Quarantine and special protocols have aggravated the hardships of life for older adults, and they experienced negative emotions in the nursing home. However, the older adults hoped that the situation would improve, and the pandemic would end.